Nominal GDP futures targeting - Sumner, Scott (Journal of Financial Stability, 2015)
Central banks have recently done a poor job of stabilizing the path of nominal expenditures. The adverse demand shock of 2008–2009 led to a severe recession in the United States and Europe. Monetary policy could be greatly improved with a regime of “targeting the forecast,” or setting policy so that the expected growth in nominal GDP is equal to the central bank's target growth rate. This goal could be accomplished by setting up a nominal GDP prediction market and then adjusting the monetary base to stabilize nominal GDP futures prices. The market, not central banks, would set the level of the monetary base and short-term interest rates under this sort of policy regime. Modest adjustments in such a regime could address many previous criticisms of futures targeting.